Pengendalian Emergency Lowering System (ELS) Pada Lift 3 Lantai - Hasby Mukamal, Irham; Sumardiono, Arif; Artdhita Fajar Pratiwi (P3M Politeknik Negeri Cilacap, 2026)
Power outages in multi-storey buildings can cause elevators to stop operating and pose safety risks to users. One effective solution to address this issue is the implementation of an Emergency Lowering System (ELS), which enables the elevator to move to the nearest floor when the main power supply fails. This study aims to design and evaluate an Emergency Lowering System (ELS) for a three-floor elevator based on an Arduino Mega, equipped with a backup power system using an inverter and battery, as well as load monitoring using a load cell sensor. The research methodology includes hardware and software design, load cell sensor calibration, and system testing under various load conditions and power outage scenarios. The experimental results show that the ELS is capable of transferring the power source with an average switching time of less than 5 seconds. The load cell measurement error was recorded at 0.16%, indicating reliable load detection. Consequently, the elevator can be safely lowered to the nearest lower floor during a power failure. These results demonstrate that the developed ELS system has strong potential to enhance the safety and operational reliability of small-scale elevators, particularly in low-rise buildings.